PORTRAITURE OF ASHTA-NAYIKAS DESCRIBED FROM RASIKPRIYA IN PAHARI STYLE - Gupta, Sheril (ShodhKosh: Journal of Visual and Performing Arts, 2024)
’Rasikpriya Granth’ is a supramundane representation of Ashta-Nayika poetry. This awe-inspiring genre has diffused love in Pahari areas. In order to propagate the beauty of Rasikpriya, the Eight Nayikas imbued in ’Shringar Rasa’ have been depicted in an emotionally charged manner by the contemporary poet Keshavdas. Pahari painters inspired by the poesy have expressed the youthfulness of these Nayikas in a charmingly artistic way. Accordingly, the painters have manifested their abstract feelings and enlivened the Ashta-Nayikas through their ideational strokes. It seems that every little particle of these miniature paintings sing the lyric of love. The Pahari-style miniatures have creatively shown the element of divine love in an attractive manner. Reasonably, this portrayal has touched the hearts of art lovers.